2002
DOI: 10.1111/j.1944-9720.2002.tb03151.x
|View full text |Cite
|
Sign up to set email alerts
|

Surfing to Cross‐Cultural Awareness: Using Internet‐Mediated Projects to Explore Cultural Stereotypes

Abstract: The Standards for Foreign Language Learning in the 21st Century stress that learning about culure is an integral part of learning a foreign language (L2); such exploration is a necessary bridge to gaining valuable insights about one's own culture as well as the culture(s) of the target language. Long‐term projects, for example, extended interviews with native speakers, enable learners to develop an understanding of another culture from an “emic” point of view (Barro et al., 1993; Robinson‐Stuart & Nocon, 1996;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 16 publications
4
58
1
2
Order By: Relevance
“…The authors distinguished eight main categories among the students' stereotypes, namely: (i) the Germans' love of beer, (ii) the personal characteristics of the German people, (iii) cars, (iv) the country or language, (v) schooling or culture, (vi) physical attributes, (vii) history or historical events, and (viii) food and eating. Studies by Taylor (1977), Webber (1990) and Abrams (2002) on learners of German in American colleges reported similar fi ndings; the students frequently made statements about the German people's love of beer and also made references to their food, culture (e.g., folklore, classical music), national traits and school system. Various studies have concluded that language learners' images about Germany and the Germans are highly stereotypical.…”
Section: Country Image and Stereotypesmentioning
confidence: 52%
See 3 more Smart Citations
“…The authors distinguished eight main categories among the students' stereotypes, namely: (i) the Germans' love of beer, (ii) the personal characteristics of the German people, (iii) cars, (iv) the country or language, (v) schooling or culture, (vi) physical attributes, (vii) history or historical events, and (viii) food and eating. Studies by Taylor (1977), Webber (1990) and Abrams (2002) on learners of German in American colleges reported similar fi ndings; the students frequently made statements about the German people's love of beer and also made references to their food, culture (e.g., folklore, classical music), national traits and school system. Various studies have concluded that language learners' images about Germany and the Germans are highly stereotypical.…”
Section: Country Image and Stereotypesmentioning
confidence: 52%
“…Researchers and language educators agree that enhancing students' critical and theoretical thinking is one of the most important elements in the teaching of the Humanities and Social Sciences disciplines (Abrams, 2002;Byram and Kramsch, 2008;Ferreira, 2003). As Schulz and Haerle (1995, p. 29) have pointed out, one of the most important objectives of foreign language education "is the lessening of preconceived stereotypical images regarding the target culture".…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abrams, 2002;Belz, 2002Belz, , 2005Ware, 2005), research on teachers and their teaching of IC has been rather scarce (Doğançay-Aktuna, 2005;Byram & Kramsch, 2008;Kohler, 2015;Sercu, 2006;Sercu et al, 2005). Of this research, only few studies have been conducted on FL teachers other than English (FLOTE).…”
Section: Literature Reviewmentioning
confidence: 99%